EMBRACING PROJECT-BASED LEARNING (PBL): A TRANSFORMATIVE METHODOLOGY FOR 21ST CENTURY EDUCATION - Jalolova Muqaddas; Toshtemirova Nilufarkhon Ashurali kizi (TADQIQOTLAR, 2025)
Abstract: Project-Based Learning (PBL) is a dynamic, student-centered pedagogy that encourages learners to gain knowledge and skills by working over an extended period to investigate and respond to authentic, engaging, and complex questions, problems, or challenges. Unlike traditional methods, PBL fosters deep learning, critical thinking, collaboration, and real-world application of knowledge. This article explores the key features, benefits, and implementation strategies of PBL, alongside its relevance in modern education. It also addresses the challenges educators face while adopting this approach and provides recommendations for effective practice.